AN ANALYSIS OF MAXIM VIOLATION IN SITUATIONAL COMEDY THE BIG BANG THEORY SEASON 11 - Andreas Novebry; Rusdi Noor Rosa (Universitas Negeri Padang, 2019)
In an effective and efficient communication, speakers and listeners are required to work together to build a good conversation by considering the principles proposed by HP Grice in 1975. He categorizes the maxim into four types, namely maxim of quantity, maxim of quality, maxim of relation and maxim of manner. This paper tries to find out the maxim violations and characters’ reason to violate it in situational comedy “The Big Bang Theory Season 11”. Qualitative method was used for this research. The result shows that there were 140 violated utterances found in 336 scenes from 12 episodes: violation of maxim quantity (31.4%), violation of maxim quality (17.1%), violation of maxim relation (27.8%), violation of maxim of manner (20%), and multiple maxim violation (3.5%). Also, the researcher found that some indicators to identify the reason of maxim violation based on the guidelines from Tupan and Natalia (2008) and Christoffersen (2005) were not found such as avoiding to hurt the hearer, building one’s believe, and convincing the hearer (violation of maxim quality), Do the wrong causality (violation of maxim relation), and voice is not loud enough (violation of maxim manner).Key words: Maxim Violation, Sitcom TBBT